Identifying the Difficulties of Using Punctuation Marks in Writing Among Grade Ten Students in Kalmunai Muhammad Ladies College - I.S Ismath Farjana; Mohamed Jabeer Fathima Sujani; MR. Rishad Muhammed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The correct use of punctuation mark is a key skill in writing. It forms an important part of written language and plays a very important role in giving intended meaning to the language. The use of a wrong mark of punctuation or even a wrong placement of mark of punctuation can change the meaning of a sentence completely and lead to confusions. This study investigates Identifying the difficulties of using punctuation marks in writing among the grade ten students in Kalmunai Mahmud Ladies College. It presents the method which includes a questionnaire and tests for students. Data was collected both from the questionnaire the questionnaire and the results of tests such as pre- test and post test given to students. The results showed that the KM/ Mahmud Ladies College students had difficulty in identifying punctuation marks in writing. Moreover, it was identified that the teaching method could be changed and improved so as to make the students understand. At last, the s tudents showed improvement in their understanding of punctuation marks and its application after second language learners learnt punctuation marks through the new teaching method.